Evaluation of Complementary Effects of Exogenous Fibrolytic Enzymes and Fumaric Acid on Methane Emission and Ruminal Fermentation by In Vitro Method - Sudheer Babu, Arumbaka; Mohini, Madhu; Singh Thakur, Sudarshan; Mondal, Goutam (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The objective of the present study was to investigate the hypothesis that exogenous fibrolytic enzymes (EFE, Cellulase with activity >4500-5000 µM glucose/g/min and Xylanase with activity >7500-8000 µM xylose/g/min, mixed in 50:50 w/w), in combination with fumaric acid (FA) and sodium sulfate (SS) may provide complementary effects to mitigate methane emission and enhance in vitro fermentation parameters of a sorghum stover based substrate (60% roughage and 40% concentrate). Three levels of EFE (0, 0.75 and 1.5 g/kg DM) (E0, E1 and E2) with two levels of FA (F0 and F1) @ 0 and 8 mM (or 0 and 2 % of DM) and SS (S0 and S1) @ 0 and 1 g/kg DM, were tested in 3x2x2 factorial design using in vitro gas production technique. E1 level reduced the methane production and improved TDDM (%) significantly while the combination of E1 level with F1 reduced methane % along with enhanced TDDM and TDOM (%). Fumarate alone was not efficient to decrease methane levels and increase digestibility but its combination with E1 level showed the desired effects. Other levels (S1 with E1 and S1F1 with E1) reduced methane but TDDM (%) and TDOM (%) were reduced. Overall, the in vitro results of fumaric acid in combination with EFE 0.75 g/kg DM can provide a possible strategy for mitigation of enteric methane emission to be proved by in vivo experiments.